Influence of Fining and Tartaric Stabilisation Procedures on White Wine Mannoprotein Content - Rodrigues, A.; Ricardo-Da-Silva, J.M.; Lucas, C.; Laureano, O. (South African Journal of Enology and Viticulture, 2016)
Limpidity is a major quality attribute in white wine appreciation. After alcoholic fermentation and ageing, white wines are normally subjected to protein and tartaric stabilisation, followed by filtration. The impact of bentonite and gelatine fining and cold static tartaric stabilisation on the mannoprotein content of two white wines was studied. All treatments promoted a decrease in the content of mannoproteins. Bentonite fining largely affected the mannoproteins with the highest molecular weight, as did cold static tartaric stabilisation and gelatine fining.